Validity and reproducibility of a food frequency questionnaire to assess lipid and phytochemical intake - Perovic, Nilda R. (2015)
Background: epidemiological studies have been related food intake with the incidence of nontransmissible chronic diseases. Objective: the purpose of the present study was to analyze the validity and reproducibility of a food frequency questionnaire (FFQ) aimed at assessing lipid and phytochemical intake. Material and Methods: FFQ was administered to 45 people of both sexes, aged between 20 and 72 years old and resident in Cordoba, Argentina. The FFQ included 257 questions referring to foods, their consumption frequency and portion size. Regarding consumption of fruit and vegetables, the season was also taken into account. The questionnaire was applied at two different periods (FFQ1 and FFQ2) with a break of six months in between. As a reference, the 24-hour dietary recall was used (24HDR) three times. The mid intake of FFQ1-FFQ2, the 24HDR-FFQ2 median intake, median difference, Mean Absolute Deviation from the median differences (MAD), Wilcoxon signed rank sum test and Spearman rank order correlation coefficients were calculated to analyze the accuracy of the FFQ data. Results: the correlation coefficients for FFQ1-FFQ2 varied from 0.52 for 20:5 n3 eicosapentanoic (EPA) fatty acid to 0.89 for 4:0 butyric fatty acid (p<0.05). For 24HDR-FFQ2, the values ranged from 0.19 for lycopene to 0.93 for EPA fatty acid (p<0.05). Conclusion: the analysis carried out showed an acceptable validity and reproducibility of the FFQ, thus enabling it to be used in research relating the intake of lipids and phytochemicals and the risk of non-transmissible diseases.